120k views
0 votes
I'm stuck on this one. I'm sorry of you know everything but there are other people who can't comprehend some problems without being their to actually see and experience it with a teacher. Just help me with this one - ​

I'm stuck on this one. I'm sorry of you know everything but there are other people-example-1
User Yusufk
by
6.1k points

1 Answer

4 votes

Answer:

Expand the brackets, and simplify.

(4t - 8/5)-(3-4/3t) = (4t +4/3t) + ( -8/5 - 3) = 5 1/3t - 23/5 = 16/3t - 23/5

5(2t + 1) + (-7t + 28) = 10t + 5 - 7t + 28 = 3t + 33

(-9/2t + 3) + (7/4t + 33) = (-9/2t + 7/4t) + (3 + 33) = -11/4t + 36

3(3t - 4) - (2t + 10) = 9t - 12 - 2t - 10 = 7t - 22

User Tmr
by
6.2k points